Comammox Nitrospira within the Yangtze River continuum: community, biogeography, and ecological drivers - Shufeng Liu; Haiying Wang; Chen, Liming; Wang, Jiawen; Zheng, Maosheng; Liu, Sitong; Qian Chen; Ni, Jinren (Isme JournalIsme Journal, 2020)
The recent discovery of comammoxNitrospiraas complete nitrifiers has fundamentally renewed perceptions of nitrogen cycling in natural and engineered systems, yet little is known about the environmental controls on these newly recognized bacteria. Based on improved phylogenetic resolution through successful assembly of ten novel genomes (71-96% completeness), we provided the first biogeographic patterns for planktonic and benthic comammoxNitrospirain the Yangtze River over a 6030 km continuum. Our study revealed the widespread distributions and relative abundance of comammoxNitrospirain this large freshwater system, constituting 30 and 46% of ammonia-oxidizing prokaryotes (AOPs) and displaying 30.4- and 17.9-fold greater abundances than canonicalNitrospirarepresentatives in water and sediments, respectively. ComammoxNitrospiracontributed more to nitrifier abundances (34-87% of AOPs) in typical oligotrophic environments with a higher pH and lower temperature, particularly in the plateau (clade B), mountain and foothill (clade A) areas of the upper reach. The dominant position of planktonic comammoxNitrospirawas replaced by canonicalNitrospirasublineages I/II and ammonia-oxidizing bacteria from the plateau to downstream plain due to environmental selection, while the dissimilarity of benthic comammoxNitrospirawas moderately associated with geographic distance. A substantial decrease (83%) in benthic comammoxNitrospiraabundance occurred immediately downstream of the Three Gorges Dam, consistent with a similarly considerable decrease in overall sediment bacterial taxa. Together, this study highlights the previously unrecognized dominance of comammoxNitrospirain major river systems and underlines the importance of revisiting the distributions of and controls on nitrification processes within global freshwater environments.